PENINGKATAN SELF ESTEEM SISWA MELALUI KOMBINASI TEKNIK RESTRUKTURISASI KOGNITIF DAN VISUALISASI - Akhmad Harum (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
approach with cognitive restructuring and visualization techniques. This study uses a quantitative approach. The method used is a quasi-experimental research design with nonequivalent pretest-posttest control group design. Data collection techniques were carried out using a self-esteem questionnaire. The research sample is the class students of SMPN 13 Makassar in the academic year 2021/2022 who have low self-esteem with purposive sampling technique. Data analysis technique using t test. The results showed that the self-esteem level of the students of SMPN 13 Makassar, based on the results of the pretest on experimental and control subjects, showed that some indicators of self-esteem were adequate and others were still minimal. There are 3 aspects consisting of cognitive aspects in the high category, affective and evaluative aspects in the medium category. There are 19 aspects consisting of 6 indicators are in the high category and 13 indicators are still in the medium category. The treatment for the medium category indicator is focused on increasing towards the high category and the high category will be given treatment as reinforcement. The cognitive-behavioral modification approach with cognitive restructuring and visualization techniques is effective in increasing students' self-esteem. The increase can be seen from the posttest results, namely there are 7 aspects of effective self-esteem increasing. So the cognitive behavioral modification approach with cognitive restructuring and visualization techniques is effective in increasing the self-esteem of students at SMPN 13 Makassar Keywords: self esteem, visualization, behavior modification